Developing e-Commerce of Unique Indonesian Souvenirs with Web Engineering - Cholid Fauzi; M. Hoeru Riza (IJISTECH (International Journal of Information System and Technology), 2021)
E-Commerce Unique Regional Souvenirs in Indonesia is a buying and selling application made to make it easier for tourists to find a place or location for typical regional gifts and make it easier for tourists to order souvenirs during a pandemic like now, as well as a means for traveler's local souvenir sellers to promote their products online. Making regional e-commerce specialties in Indonesia uses the Web Engineering paradigm and system modeling with UML (unified modeling language) with business cases, activities, use cases, and class diagrams. At the same time, the database management software uses MySQL with the PHP programming language and the Laravel Framework. The system design is expected to make it easier for people to find local souvenirs based on the place or location of souvenir merchants and local souvenir sellers to promote their products online